Penggunaan Pendekatan Creative Problem Solving dalam Peningkatan Ketuntatasan Belajar Mata Pelajaran Penddiikan Agama Islam: Studi Kualitatif Deskriptif di SMAN 1 Cibitung Bekasi - Muhammad Sholeh; Wisnawati Loeis (Program Studi Pendidikan Agama Islam, Fakultas Agama Islam UNISMA Bekasi, 2016)
The problem of this research is how using creative problem solving approach in improving learning lesson in Islamic religoius education at SMAN (Senior High School) 1 Cibitung Bekasi? Through qualitative method, this research shows that the use of creative problem solving approach in improving students' mastery learning is a good fit for purpose. Increased mastery learning students can be seen from a good student achievement, according to the standards of completeness that determined. Advocates factor the use of creative problem solving approach in improving students' mastery learning are educators, learners, parents, media, education, and environmental factors of education. While inhibiting the use of creative problem solving approach in increasing mastery learning is the diversity of learners and the uneven background of religious knowledge held by students.